2015
DOI: 10.1038/srep17955
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature-grown continuous graphene films from benzene by chemical vapor deposition at ambient pressure

Abstract: There is significant interest in synthesizing large-area graphene films at low temperatures by chemical vapor deposition (CVD) for nanoelectronic and flexible device applications. However, to date, low-temperature CVD methods have suffered from lower surface coverage because micro-sized graphene flakes are produced. Here, we demonstrate a modified CVD technique for the production of large-area, continuous monolayer graphene films from benzene on Cu at 100–300 °C at ambient pressure. In this method, we extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 38 publications
0
74
0
1
Order By: Relevance
“…In addition, the preformation of these cyclic carbon ring structures means that the nucleation and coalescence processes that are required to form graphene are energetically more facile than when aliphatic precursors are utilised [45]. The graphene growth mechanism then proceeds via the systematic attachment of these C 6 fragments to the growth front of the monolayer graphene sheets [46]. This proposed mechanism is supported by results for the dechlorination and subsequent graphene formation of hexachlorobenzene on copper foils [47].…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…In addition, the preformation of these cyclic carbon ring structures means that the nucleation and coalescence processes that are required to form graphene are energetically more facile than when aliphatic precursors are utilised [45]. The graphene growth mechanism then proceeds via the systematic attachment of these C 6 fragments to the growth front of the monolayer graphene sheets [46]. This proposed mechanism is supported by results for the dechlorination and subsequent graphene formation of hexachlorobenzene on copper foils [47].…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…It is a one atom thick sheet made of sp 2 carbons arranged in a honeycomb lattice that was firstly obtained by mechanical exfoliation of pyrolytic graphite [8]. However, despite its remarkable properties and variety of applications it is not trivial the production of pristine graphene in large areas, even considering recent advances in chemical vapour deposition (CVD) methods [9] that require high temperatures (300 -500 o C) and expensive equipment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Marchena et al have achieved direct graphene growth on exible glass at 700 C. 12 Sulaiman et al and Jang et al demonstrated CVD graphene growth on Cu at 450 and 300 C by using chlorobenzene and benzene, respectively, as a carbon source. 13,14 The ion bombardment of solid surfaces is well-known to entail the formation of nano structures even at room temperature, such as ripples, pyramid, conical protrusions (cones) and whiskers. [15][16][17] So, the ion irradiation has a great potential for the room temperature fabrication of nanostructured materials.…”
Section: Introductionmentioning
confidence: 99%